Keanekaragaman Spesies Burung Di Repong Damar Pekon Pahmungan Kecamatan Pesisir Tengah Krui Kabupaten Lampung Barat - A.Basyir Firdaus; Agus Setiawan; Elly Lestari Rustiati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Repong Damar is a management system in cultivated area by local community of Krui. It has great biodiversity and plays an important role as avian natural habitat. This research was conducted to learn the diversity of bird species in Repong Damar using concentratedmethod in four different locations: area between padi field and forest, settlement area, opened damar forest, and damar forest. Three replications were done on each location. There are 16 birds species of 10 families (N=468). The highest diversity index was indamar forest (H’= 1.082), and the lowest was in opened damar forest (H’= 0.502). Keywords: bird, diversity index, repong damar